Ημερήσια πορεία του σημείου εξωτερικού περιβάλλοντος στον ψυχρομετρικό χάρτη και απαιτούμενη ενέργεια για είσοδο στη χειμερινή και θερινή ζώνη θερμικής άνεσης περιοχής Αθηνών - Αλωνιστιώτη, Δέσποινα (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Μηχανολόγων Μηχανικών. Τομέας Θερμότητας, 2017)
The present thesis disseminates the topic of thermal comfort, emphasizing the evaluation of the thermal environmental conditions in the area of Athens. The specific project consists of two parts. The first part is a theoretical approach of the basic aspects related to thermal comfort. Initially, the mechanisms of the human organism that contribute to its adaptation to the environment are mentioned. Additionally, the basic factors of thermal comfort and the indicators used in the process of assessing the thermal conditions in indoor and outdoor environments are analyzed. Finally, a reference of the international standards used in the research on the thermal conditions of an area is presented. In the second part, the thermal ambient air conditions of Athens are calculated for the 24-hour period of the 21st day of each month and for all months of the year. The ultimate goal is to calculate the energy that must be removed or attributed to convert the environmental conditions of Athens into a thermally comfortable environment. These calculations are made initially for each hour individually and in the end conclusions for the whole period of 24 hours for each month are drawn.